2020
DOI: 10.1080/14656566.2020.1829594
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological treatment of focal epilepsy in adults: an evidence based approach

Abstract: Introduction:Focal seizures represent the most common seizure type and focal epilepsies the most common epilepsy type. Anti-seizure medications (ASMs) still represent the main form of treatment for epilepsy. Areas covered:The aim of this review article is to provide an overview of available evidence about current and upcoming pharmacological options and strategies for adults with focal epilepsy focusing on the last 5 years.Expert opinion: Seventeen drugs are currently approved for the treatment of focal seizur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 58 publications
0
6
0
1
Order By: Relevance
“…The next most frequently tested ASM in our case series was LTG with 727 samples, followed by ESM, PB, PHT, TPM, and LCS. Some studies have indicated LTG as a first-choice option for focal and generalized seizures, and this ASM is very popular, especially in the UK [ 17 , 18 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The next most frequently tested ASM in our case series was LTG with 727 samples, followed by ESM, PB, PHT, TPM, and LCS. Some studies have indicated LTG as a first-choice option for focal and generalized seizures, and this ASM is very popular, especially in the UK [ 17 , 18 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…of patients with epilepsy are unable to achieve seizure control with currently available anti-epilepsy drugs (AEDs), and the introduction of multiple new drugs over the last two decades has done little to change this (Mula 2020). All current AEDs only suppress seizures, with none confirmed to stop or reverse the process that converts a healthy brain into an epileptic brain, that is, epileptogenesis (Löscher and Brandt 2010).…”
Section: Other Biomarkers In Epilepsymentioning
confidence: 99%
“…Hence, testing novel herbal-based candidates is encouraged to overcome these obstacles. Overall, evidence on specific drug combinations remains rare and a combination of routine antiseizure medications with novel candidates such as herbal-based extracts such as cannabidiol (CBD) deserves further investigation ( 8 ).…”
Section: Introductionmentioning
confidence: 99%